EFEKTIVITAS TEKNIK BEHAVIOR CONTRACT DALAM MEREDUKSI TOXIC LANGUANGE PADA SISWA SMK AR-RIFAIYAH (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to determine the effectiveness of the behavior contract technique as an effort to reduce toxic language in Ar-Rifayah Vocational High School students. This study uses a quantitative experimental approach with the T-test (paired sample T-test) method. Data collection techniques used are questionnaires, observation and documentation. The data analysis technique of this study uses descriptive analysis and inferential analysis of the T-test (paired sample T-test) to test the research hypothesis. The results showed that there were 12 Ar-Rifayah Vocational High School students who became the research sample. Based on the results of the analysis conducted by the researcher, the significance value of the T-test (paired sample T-test) the researcher obtained a significance value (2-tailed) of 0.000 <0.5, so in this study the researcher concluded that Ha was accepted and Ho was rejected, because the behavior contract technique was proven effective in reducing students' toxic language and there was a significant difference in the level of toxic language of students before and after being given treatment in the form of group counseling services using the behavior contract technique at Ar-Rifayah Vocational High School.